Éducation à la laïcité et enseignement laïque du fait religieux : enjeux d’une pédagogie du discernement - Anne Vézier (Éducation et Socialisation)
The reference to the principle of secularism, secular education, the religious fact respectful of beliefs or non-beliefs. The discovery and acceptance of religious pluralism contribute to living together in tolerance and respect for the pluralism of beliefs (Willaime, 2017). This teaching would serve to live together, according to the principle inherited by Condorcet that there can be no conflict between knowledge and values ​​(Audigier, 1991). An educational aim which institutes tolerance and respect for the pluralism of beliefs risks, however, making the support of critical reason as an accessory, if the teaching of the religious fact does not rely on the teaching of the scientific approach that allows to speak of religious fact. The analysis of a teaching situation on medieval religious pluralism raises questions about the conditions for questioning how values ​​are to be understood. With this study, we seek to build benchmarks to help teachers to problematize these situations where values ​​and knowledge are in tension.